2008
DOI: 10.1200/jco.2007.13.9030
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adjuvant Cisplatin Evaluation: A Pooled Analysis by the LACE Collaborative Group

Abstract: Postoperative cisplatin-based chemotherapy significantly improves survival in patients with NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
1,497
6
45

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,139 publications
(1,658 citation statements)
references
References 34 publications
41
1,497
6
45
Order By: Relevance
“…The magnitude of the benefit in the current study (HR, 0.82) is comparable to that observed in clinical studies (HR, 0.89). 10 We further noted that this association varied by AJCC stage and time period of diagnosis. Carboplatin was the primary platinum agent used in the adjuvant setting and the combination of carboplatin and paclitaxel These rates may be underestimated due to our use of registry and administrative data, which do not capture the reasons patients may not be eligible for AC.…”
Section: Discussionmentioning
confidence: 65%
“…The magnitude of the benefit in the current study (HR, 0.82) is comparable to that observed in clinical studies (HR, 0.89). 10 We further noted that this association varied by AJCC stage and time period of diagnosis. Carboplatin was the primary platinum agent used in the adjuvant setting and the combination of carboplatin and paclitaxel These rates may be underestimated due to our use of registry and administrative data, which do not capture the reasons patients may not be eligible for AC.…”
Section: Discussionmentioning
confidence: 65%
“…Chemotherapy, specifically platinum-based regimens, have been proven beneficial to survival after lobectomy in patients with more advanced stage NSCLC, especially those with lymph node spread. The Lung Adjuvant Cisplatin Evaluation meta-analysis analyzed data from the five largest RCTs investigating cisplatin-based regimens after complete resection and found a 5-year absolute survival benefit of 5.4% with adjuvant chemotherapy (31). However, this benefit varied considerably with stage; the meta-analysis showed that the majority of the survival benefit came from treating stage II (HR, 0.83; 95% CI, 0.73-0.95) and stage III (HR, 0.83; 95% CI, 0.72-0.94) NSCLCs, whereas patients with stage IA tumors (<3 cm in size; HR, 1.40; 95% CI, 0.95-2.06) had worse outcomes when treated with adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based adjuvant chemotherapy is mostly used for these patients. Studies presented that the platinum-based chemotherapy can decrease mortality by 11% and improve five year survival by 5.4% (Pignon et al, 2008). However, patients respond differently to platinum drugs (Bahland Falk, 2001).…”
Section: Introductionmentioning
confidence: 99%